PELAKSANAAN KEGIATAN PENGENDALIAN PENYAKIT PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS I PURWOKERTO TIMUR TAHUN 2018 - Siti Hidayatul Majidah; Aris Santjaka (Poltekkes Kemenkes Semarang, 2019)
By 2015 the WHO reports nearly six million children under five die and 16% of that number is caused by pneumonia as the number one killer of children under five in the world. Pneumonia is a respiratory disease that is still a public health problem. In 2016 found 3,005 cases of Pneumonia that occurred in Banyumas district. Pneumonia is a lot of happening in East Purwokerto area, which found 274 cases. The main purpose of this study is to provide an overview of the implementation of Pneumonia disease control activities in under-five children in terms of surveillance, determinants and control efforts. The research method was the descriptive method and the subjects were puskesmas office and 20 patients with Pneumonia. The general and specific data was collected through interview, observation, and field measurement. By 2015 until 2017 pneumonia sufferer detection coverage could not reach the target. The research result shows Pneumonia patient consist from 11 men (55%) and 19 women (45%). Pneumonia commonly occur toward 1-5 years old group of age. Pneumonia sufferers mostly occur in patients who have homes that do not meet the conditions of ventilation and lighting conditions that do not meet the requirements. The highest number of patients in the Arcawinangun area was 13 patients and the peak incidence of pneumonia occurred in April, ie 5 people (25%). Based on research, in addition to overcome Pneumonia, Puskesmas further increase the sufferer detection of Pneumonia's discovery and for the society if they will build a house or will renovate the house need to pay attention to the aspect of healthy house and provide a complete immunization toddler